Sosialisasi Dampak Bullying di SMKN 1 Pemulutan - Mutia Mawardah; Peni Hutami (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Bullying cases are familiar to mass media observers. On television electronic media, broadcasters explain via radio electronic media, and journalists write about it in various newspapers. Often the law and government are not quick and careful in handling bullying cases in Indonesia. The method of carrying out activities is using the socialization method, which is a process of learning the roles, status and values needed for participation in social institutions, from the results of the implementation of socialization for students at SMKN 1 Pemulutan now have a better understanding of the concept of bullying and the negative impacts that this behavior may have. The implementation of community service allows students to remember how to prevent bullying more effectively.